Basic democracies in den Chittagong Hill Tracts, Ostpakistan - Löffler, Lorenz G. (Sociologus, 1968)
The Chittagong Hill Tracts are populated by ethnic minorities, different by culture and religion from the muslim-Bengal majority of Eastern Pakistan. Their various forms of socio-political organization had been unified, to a certain degree, by the former British administration. A feature of long standing which remained was the authority based on prestige gained by "giving away" — during feasts and on other occasions. Thus, the overall pattern is: giving away creates (or strengthens) social dominance; receiving diminishes (or prevents) it, insofar as it creates a situation of dependence on the givers. In the course of time, this system has been locally corrupted, but it has nowhere wholly disappeared. In 1959, a political institution hitherto unknown was introduced: the universal, equal and secret ballot of local representatives. The results disclose a syncretism of traditional conceptions with new ones. The scheme of measuring influence and power on the basis of giving and receiving, for instance, generally remained. On the other hand, there seem to be no traditionalistic biases regarding progressive development (in the sense of a general improvement of economic and social conditions) and preference for candidates to be elected (i. e., for those belonging to the traditional elite). The votes show a strong tendency to uphold the respective cultural identities of the voting groups, but there are also signs of an improvement of understanding between ethnic majorities and minorities. On the whole, it seems that this system of Basic Democracies may well prove itself to be a meaningful and positive contribution.